Augmented compliance intention through the appropriation of compliance support systems - Kim, Sang Soo; Kim, Yong Jin (Behaviour & information technology, 2022)
Under today's complex and ever-changing regulatory environment, only forcing employees into compliance by wielding control or imposing punishment does not automatically lead to improved compliance awareness and performance. Based on the adaptive structuration theory and theory of planned behaviour, this study investigated the effect of Compliance Support Systems (CSS) appropriation on compliance intention. A two-stage survey was conducted to see whether the continuous use of CSS enhances users' intention to comply with laws and regulations. This approach comes under longitudinal research because it seeks to discover the causality between variables by observing research subjects at different times. The PLS-SEM analysis verified the direct and indirect impact of compliance behavioural beliefs and social pressure on compliance intention. In particular, the two factors were found to affect CSS appropriation by way of CSS quality and compliance knowledge. The proposed structural model was developed to compare the gaps of perception in different measurement times. Therefore, the findings highlight a significant role of CSS appropriation in raising compliance intention and provide practical insights by presenting the factors that enhance employees' positive and voluntary engagement in compliance behaviour.